AMBISI EKSPANSI BISNIS DAN POLITIK STRATEGIS CINA DI ASIA TENGGARA MELALUI BELT ROAD INITIATIVE: TINJAUAN DIPLOMASI INFRASTRUKTUR - Aspin Nur Arifin Rivai (UIN ALAUDDIN MAKASSAR, 2022)
China's success is due to the Go Out policy. Xi Jinping became the party that gave China a new form in regional and world competition through the Belt Road Initiative cooperation campaign. This cooperation has convergence with the interests of Southeast Asian countries, on the one hand they want deepening economic cooperation facilities, on the other hand infrastructure development assistance. This research uses an infrastructure diplomacy approach which assesses that the promotion of cooperation offered by China to Indonesia, Malaysia and the Philippines cannot be seen as an ordinary form of cooperation, but as an effort by Beijing's administration to build a hegemonic image in the Southeast Asian region based on geo- economy, while on the commercial side BRI's presence is a continuation of the Go Out policy, namely the internationalization of SOEs in infrastructure development cooperation relations.